Potensi Geodiversity Daerah Oluhuta Kecamatan Kabila Bone Kabupaten Bone Bolango Menggunakan Asesmen - Ponto, Nadia Fransisca; Arifin, Yayu Indriati; Hutagalung, Ronal; Akase, Noviar; Manyoe, Intan Noviantari (Journal of Applied Geoscience and Engineering, 2023)
Geotourism emphasizes the beauty, uniqueness, rarity and wonder of natural phenomena as an impetus for the development of geology-based tourism. The many variations in geological aspects fulfill the potential geodiversity value in the area. The aim of this research is to identify and assess the potential for geodiversity in Oluhuta Village. The research location has coordinates 0° 25' 0" - 0° 27' 0" N and 123° 8' 30" - 125° 10' 30" E. There are several research methods used in the form of field observations, laboratory research, and processing studios. The geological data obtained includes lithology, geomorphology and assessment of geodiversity aspects. The results of the research show that the location of the research area has lithology namely reef limestone and geomorphology namely reef terrace plains. The research area has a site called the Lautan Terangkat Site. This site has geological components including rocks and natural landscapes. Lautan Terangkat site have several assessment criteria with a total number and scientific assessment classification. Scientific value assessment is classified as medium, the educational value assessment is classified as high, tourism value assessment is classified as medium, and the assessment of degradation risk value is classified as low.